Nghiên cứu thành phần hóa học Mallotus philippensis - Mai, Nguyễn Thị; Minh, Châu Văn; Kiệm, Phan Văn; Khôi, Nguyễn Hữu; Cường, Nguyễn Xuân; Đăng, Nguyễn Hải; Thảo, Nguyễn Phương; Nam, Nguyễn Hoài; Mỡi, Lã Đình; Bản, Ninh Khắc (Vietnam Journal of Chemistry, 2012)
From the methanol extract of the Mallotus philippensis leaves, platanoside (1), 4-dihydro-myricetin (2), isovitexin (3), pachysandiol A (4), and dopaol (5) were isolated by various chromatoghraphy methods. Their structures were elucidated by ESI-MS and NMR experiments. This is the first report of 1 - 5 from M. philippensis.